2018
DOI: 10.1186/s12889-018-6269-9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood road traffic injuries in Canada – a provincial comparison of transport injury rates over time

Abstract: BackgroundIn Canada, road traffic injuries are the leading cause of death among children and youth ≤19. Across the country, there is variability in road traffic injury prevention policies and legislation. Our objective was to compare pediatric road traffic related injury hospitalization and death rates across Canadian provinces.MethodsPopulation-based hospitalization and death rates per 100,000 were analyzed using data from the Discharge Abstract Database and provincial coroner’s reports. Road traffic related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…These may include households' wealth, consumption expenditure, or assets. Ranking households based on their income alone, might have some misleading outcomes in interpreting the results [23,24].…”
Section: Principal Findingsmentioning
confidence: 99%
“…These may include households' wealth, consumption expenditure, or assets. Ranking households based on their income alone, might have some misleading outcomes in interpreting the results [23,24].…”
Section: Principal Findingsmentioning
confidence: 99%
“…From 1991 to 2015, the death rate attributable to road traffic injuries among children and adolescents aged 1 to 14 years in Ireland decreased from 2.10/100,000 to 0.32/100,000 [23] . From 2006 to 2012, the incidence of road traffic injuries in Canadian children was 70.91/100,000, and the hospitalization rate for injuries decreased from 85.51/100,000 to 58.77/100,000 [24] . With the implementation of the global "traffic safety promotion", the use of seat belts and appropriate child safety seats has steadily increased, and the production of safer cars, better road construction, and increased public awareness of driving risk behaviors have reduced road traffic injuries among children and adolescents [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with findings from Statistics Canada, motor vehicle traffic injuries were the leading cause of death among youth and rates fell (Ramage‐Morin 2008). In their recent paper, Fridman et al (2018) propose that the policy of graduated driver's licensing, which requires new drivers to advance through a number of learning phases, has resulted in more experienced and knowledgeable drivers on the road, contributing to a drop in deadly unintentional injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Statistics Canada (2018b) reports that unintentional injuries are the leading cause of death among children aged 10 to 19. Further, an analysis of provincial hospitalization discharge data (with the exception of Quebec) by Fridman et al (2018) found that all nine provinces saw a decrease in transport‐related injury mortality rates among children and youth between 2006 and 2012. The highest rates were in Saskatchewan (10.99 per 100,000) while the lowest were in Ontario (3.09 per 100,000).…”
Section: Literature Review and Backgroundmentioning
confidence: 99%